Artists and the Arab uprisings - Schwartz, Lowell; Kaye, Dalia Dassa; Martini, Jeffrey (RAND, 2013)
After decades of authoritarianism, a wave of political change and unrest began to sweep across the Middle East and North Africa in early 2011. Successful democratic transitions will not be easy and will require change in multiple spheres. This report focuses on one sphere whose power and importance is often underestimated: the artistic arena. Regional artists have the potential to positively contribute to democratic transition by shaping public debate in ways that support tolerance and nonviolence. But Arab artists are often squeezed between the bounds of acceptable discourse, set by rulers who fear freedom of expression and conservative societal groups that seek to control acceptable behavior. Although the Arab uprisings lifted some previous barriers to artistic expression, new limitations and challenges have emerged. Moreover, artists continue to lack sound funding models to support their work and face limited markets and distribution mechanisms. This research explores the challenges posed by both the state and society in the region, as well as the policy shifts that may be necessary to better support regional artists. It also suggests new strategies in which regional actors and nongovernmental organizations take leading roles in supporting these artists and their work.